Erosion of Potato Field as Affected by Drainage Canal Intervals of a Horizontal-ridge System - Purwoko Hari Kuncoro; Krissandi Wijaya; Asna Mustofa; Arief Sudarmaji; Susanto Budi Sulistyo; Christian Soolany (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2024)
Previously, horizontal-ridge system has been shown effective in reducing soil erosion. But, it could cause water logging, which is detrimental to crop growth and yield. To solve this problem, drainage canal establishment might be reasonable. However, the evidence remains scarce. In this study, effect of drainage canal intervals on the volume of runoff, soil loss, and nutrient loss (N-total and P-total) were investigated. There were 4 drainage canal intervals applied to the 12 targeted plots (each sized 3 m x 3 m): R0, R1, R1.5, and R2 namely 0 m, 1 m, 1.5 m, and 2 m, respectively. In this case, R0 had no drainage canals and taken as the control. The measured runoff, soil loss, N-total loss, and P-total loss ranged 24.714 – 0.951 m3 ha-1, 0.002 – 0.507 ton ha-1, 0.849 – 204.881 kg ha-1, and 0.685 – 176.505 kg ha-1, respectively. The results revealed that existence of drainage canal increased runoff, soil loss, and nutrient loss compared to the control. Amongst them, R1 gave the highest values of soil and nutrient losses followed by R1.5, R2, and R0 as the lowest, which was probably due to the difference in number of drainage canal existing: 12, 7, 5, and 0, respectively. In addition, it was noticeable for a sufficient data trend conformity of the measured nutrient loss to the data of soil loss, runoff, and rainfall within a positive correlation amongst them. The data further confirmed the effect of soil structure condition on the volume changes of both runoff and soil loss.